基于《国际中文教育中文水平等级标准》IBDP中文B普通课程汉字表编制研究 - Ni Hui Chun (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2026)
This study arises from the absence of a standardized Chinese character list for the IBDP Chinese B Standard Level course (hereafter “Standard Level”). Using examination papers between 2007 to 2013 as the source, a total of 2,129 Chinese characters were extracted and compared with the character list in the Chinese Proficiency Grading Standards for International Chinese Language Education (hereafter “the Standards”). Based on this comparison, the study explores the compilation of a Standard Level character list applicable to teaching practice. The findings reveal that 94% of the characters in the Standard Level examination materials overlap with those in the Standards, demonstrating a high coverage of the Standards’ character list for teaching and assessment in international curricula. The study also identifies distinct characteristics in the characters unique to the Standard Level and those unique to the Standards. As such, this paper proposes principles and procedures for constructing a categorized and graded character list consisting of three tiers: core characters, secondary core characters, and reference characters. The core character list is based on the shared characters; the secondary core list includes characters unique to the Standard Level as well as those unique to Levels 1–4 of the Standards; and the reference character list comprises characters unique to Levels 5–6 of the Standards. The resulting Standard Level character list aligns the course objectives with the Standards, addressing the gap in adapting the Standards to international curricula.